Chemical reaction and MHD flow for magnetic field effect on heat and mass transfer of fluid flow through a porous medium onto a moving vertical plate - Goud, B. Shankar; Nandeppanavar, Mahantesh M. (Zielona Góra: Uniwersytet Zielonogórski)
This article discusses the effect of heat and mass transfer in a boundary layer flow in the presence of a magnetic field of an electrically conducting and viscous fluid as it passes through a porous medium containing a heat source and a chemical reaction. By employing similarity variables, the governing equations are changed into nonlinear ordinary differential equations(ODEs).
Keywords: MHD; chemical reaction; Keller box method; magnetic field; thermal radiation